The personal touch: strategies toward personalized vaccines and predicting immune responses to them - Kennedy, Richard B. (2014)
The impact of vaccines on public health and well-being has been profound. Smallpox has been eradicated, polio is nearing eradication, and multiple diseases have been eliminated from certain areas of the world. Unfortunately, we now face diseases such as: hepatitis C, malaria, or tuberculosis, as well as new and re-emerging pathogens for which lack effective vaccines. Empirical approaches to vaccine development have been successful in the past, but may not be up to the current infectious disease challenges facing us. New, directed approaches to vaccine design, development, and testing need to be developed. Ideally these approaches will capitalize on cutting-edge technologies, advanced analytical and modeling strategies, and up-to-date knowledge of both pathogen and host. These approaches will pay particular attention to the causes of inter-individual variation in vaccine response in order to develop new vaccines tailored to the unique needs of individuals and communities within the population.